Modelagem do escoamento trifásico sólido-líquido-gás em golfadas acoplando transferência de calor e massa com a formação de hidratos - Bassani, Carlos Lange (2017)
Hydrate formation is one of the main flow assurance concerns in offshore oil and gas production due to the high cost of production interruptions or impairments. Hydrates are formed by the imprisonment of gas molecules into hydrogen bonded cages of water molecules. The high pressure and low temperature conditions needed for hydrate formation are frequently found in offshore production scenarios, where slug flow is often the prevailing flow regime. The present work uses a steady-state approach for modeling homogeneous hydrate-in-water dispersion formation on horizontal slug flow in pipelines. The consumption of the phases during hydrate formation is estimated by a kinetic model in terms of the gaswater interfacial surface and the subcooling of the system. The slug flow model is coupled with: (i) mass transfer terms so as to recalculate the velocities of the slug flow structures and (ii) heat generation terms, since hydrate formation is an exothermic process. Comparisons of the model with experimental data present an average deviation of ±20%. The model was used to analyze the effects brought by hydrate formation over the slug flow hydrodynamics and heat transfer, analyzing: velocities (superficial and structure velocities), pressure, temperature, heat transfer coefficient and unit cell geometry (region lengths and phase fractions). The model was also used to analyze the influence of the pipe inlet conditions (mixture superficial velocity, liquid loading, pressure, use of chemical inhibitors) and of the pipeline geometry (internal diameter, wall width, wall thermal conductivity) in delaying hydrate formation. Finally, the influence of hydrate deposits on the slug flow behavior (pressure, temperature, velocities, unit cell geometry) is analyzed.